(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two species of Megaphragma Timberlake (Hymenoptera Trichogrammatidae) are recorded as egg-parasitoids of Heliothrips haemorrhoidalis Bouché (Thysanoptera) in southern Italy (Thysanoptera), one of which is new and described as Megaphragma amalphitanum Viggiani.